KEBIJAKAN PEMBERATAN PEMIDANAAN PADA PELAKU KEKERASAN SEKSUAL TERHADAP ANAK DALAM PERSPEKTIF TUJUAN PEMIDANAAN - Wibowo, Ari (Jurnal Yuridis, 2017)
The existence of Law No. 23 of 2002 on Child Protection is part of the state's commitment to protect children. The Law has been amended for the second time through Perpu No. 1 of 2016. The emphasis in this second amendment is to aggravate the punishment of offender of sexual violence against children to provide a deterrent effect and prevent comprehensively the occurrence of sexual violence against children. This study used primary and secondary legal materials, with normative-juridical, policy, and philosophical approaches. This study concluded that punishment regulatin policy in Perpu No. 1 of 2016 reflects the purpose of punishment in the form of a combined theory that compromises between relative theory and retributive theory. While the policy of chemical chemistry regulation as a treatment reflects the purpose of punishment as rehabilitation.